The role of space and time in the interaction of farmers' management decisions and bee communities: Evidence from South India - Linda Steinhübel; Arne Wenzel; Prashant Hulamani; Stephan von Cramon-Taubadel; Nicole M. Mason (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2021)
CONTEXT Agricultural management systems of many smallholders in low and middle-income countries depend on services by pollinator populations. However, increased adoption of modern inputs and particularly the wide-spread use of agrochemicals threaten pollinators and smallholders' crop production. Understanding how farmers' use of modern inputs affects pollinator communities is, therefore, crucial for development efforts and the design and promotion of sustainable agricultural practices. OBJECTIVE We contribute to the still scarce literature on pollinator communities in low and middle-income countries by analyzing the link between the use of agrochemicals and wild bee populations in South India. Moreover, we capture temporal and spatial scaling in farm-pollinator relationships by explicitly analyzing effects of present, past, and neighboring agricultural management decisions on wild bee populations. METHODS Our empirical analysis is based on an interdisciplinary data set, combining information from pan trap experiments and a socio-economic survey of 127 agricultural plots in the rural-urban interface of Bangalore, India. We implemented a Poisson generalized linear model (GLM) to analyze factors influencing bee abundance and richness with a particular focus on the effects of farmers' management decisions. Present and past management were measured by the use of chemical fertilizers, pesticides, and irrigation in 2018 and during the previous years respectively. By setting up spatial weight matrices, we derived a proxy for neighboring management decisions and were able to estimate potential spillover effects. RESULTS AND CONCLUSION Our results suggest that agricultural intensification is associated with a decline of bee abundance and richness in our study area. Both time and space play important roles in explaining farm-bee interactions. We find statistically significant negative spillovers of pesticide use. With every addition percent of neighboring farmers using pesticides, bee abundance and richness decrease by up to 0.68 percent on the focal plot. Furthermore, smallholders' decisions to use chemical fertilizers and pesticides on their own plots significantly decrease the number of observed bees by about 20 percent. Also, every additional year of intensive past management reduces both bee abundance and richness by up to 8 percent. SIGNIFICANCE We provide new empirical evidence on farm-pollinator relationships in tropical low and middleincome countries. Based on our results, cooperative behavior among farmers and/or the regulation of agrochemical use seem to be crucial to moderate spatial spillovers of agricultural decision-making. Also, a rotation of extensive and intensive management seems to be an appropriate way to mitigate negative effects of agricultural intensification on bee populations.
Keywords: 330; Bee communities; India; pesticides; spillovers; temporal and spatial scales